Religious Perspectives on Suffering and Evil and Peace-Experience - Gooch, Paul W (Journal of Dharma, 1986)
One of the common moral concerns of the world's religious traditions is the question of justice. Problems of justice arise in relations between individuals, groups and nations; but they are also experienced more fundamentally in the disparity between what the faithful expect to receive and what they actually undergo at the hands of fate or God or the universe. Evil and suffering pose questions for believers which at their core are issues of universal or divine justice, and the student of religion finds that this issue deserves more attention than almost any other.